Durvalumab and tremelimumab in combination with metronomic oral vinorelbine for recurrent advanced cervical cancer: an open-label phase I/II study - Pernelle Lavaud; Esma Saada-Bouzid; Renaud Sabatier; Olivia Le Saux; Thibault de la Motte Rouge; Anthony Gonçalves; Elodie Coquan; Jean-Sébastien Frenel; Marta Jiménez; Alice Hervieu; Laurent Mathiot; François Legrand; et al. (Journal for ImmunoTherapy of Cancer)
Background The MOVIE phase I/II trial (NCT03518606) evaluated the safety and antitumor activity of durvalumab and tremelimumab combined with metronomic oral vinorelbine in patients with advanced tumors. We present the results of the recurrent advanced cervical cancer cohort.Methods Patients received tremelimumab (intravenously, 75 mg, every four weeks (Q4W); four cycles max) plus durvalumab (intravenously, 1,500 mg, Q4W; 26 cycles max) and metronomic oral vinorelbine (40 mg, every three weeks (3QW)) until disease progression. The primary efficacy endpoint was the clinical benefit rate (CBR) based on the Response Evaluation Criteria in Solid Tumors V.1.1, which was analyzed using a Bayesian approachResults A total of 31 patients were enrolled and treated in the cervical cancer cohort. The median number of previous lines of chemotherapy for advanced disease was 2 (0–6), with all (100%) and 12 (38.7%) patients pretreated with cisplatin and bevacizumab, respectively. At the data cut-off, the median follow-up duration was 12.8 (Q1–Q3, 6.1–34.6) months. The CBR was 53.1% (95% CI, 36.0% to 69.8%), using a non-informative prior distribution (beta(1, 1)). The overall response rate was 41.9%, five patients achieved a complete response (16.1%), and eight patients (25.8%) had a partial response irrespective of histological subtype or programmed death-ligand 1 (PD-L1) expression. Of the 31 patients, 28 (90.3%) experienced treatment-related adverse events (TRAEs), 13 (41.9%) reported grade ≥3 immune-related adverse events (AEs), and 13 (41.9%) reported grade ≥3 chemotherapy-related AEs. The definitive discontinuation rate due to TRAEs was 16.1%.Conclusions Dual checkpoint blockade of PD-L1 and cytotoxic T-lymphocyte-associated antigen-4 combined with metronomic oral vinorelbine demonstrated meaningful and durable clinical activity in patients with previously treated advanced cervical cancer. Toxicity was significant but manageable.